The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/cancers15030972
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Multi-Antigenic Myeloma-Specific T-Cell Assay in Patients with Monoclonal Gammopathies

Abstract: Multiple Myeloma (MM) typically originates from underlying precursor conditions, known as Monoclonal Gammopathy of Undetermined Significance (MGUS) and Smoldering Multiple Myeloma (SMM). Validated risk factors, related to the main features of the clonal plasma cells, are employed in the current prognostic models to assess long-term probabilities of progression to MM. In addition, new prognostic immunologic parameters, measuring protective MM-specific T-cell responses, could help to identify patients with short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For this reason, SPEP in patients with MC during a period of active infection requires monitoring to ascertain whether the observed MC is temporary. Moreover, it has been demonstrated that the immune system can control the proliferation of clonal plasma cells, suggesting that a protective T‐cell immunity could be important to prevent the transition from MGUS to MM 19,20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, SPEP in patients with MC during a period of active infection requires monitoring to ascertain whether the observed MC is temporary. Moreover, it has been demonstrated that the immune system can control the proliferation of clonal plasma cells, suggesting that a protective T‐cell immunity could be important to prevent the transition from MGUS to MM 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the immune system can control the proliferation of clonal plasma cells, suggesting that a protective T-cell immunity could be important to prevent the transition from MGUS to MM. 19,20 In severe COVID-19 a massive innate and adaptive immune response (the so-called cytokine storm) is often observed. The humoral immune response against SARS-CoV-2 has been confirmed by the presence of monoclonal IgG, IgA, and IgM in the days following infection in the serum of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%